Coalicion de Salud Comunitaria (COSACO): using a Healthy Community Partnership framework to integrate short-term global health experiences into broader community development. Issue 1 (December 2016) - Loh, Lawrence; Valdman, Olga; Dacso, Matthew
Abstract Background There is growing concern that short-term experiences in global health experiences (STEGH), undertaken by healthcare providers, trainees, and volunteers from high income countries in lower and middle income countries, risk harming the community by creating a parallel system of care separate from established community development efforts. At the same time, the inclusion of non-traditional actors in health planning has been the basis of the development of many Healthy Community Partnerships (HCP) being rolled out in Canada and the United States. These partnerships aim to bring all stakeholders with a role to play in health to the table to align efforts, goals and programs towards broad community health goals. Results This methodology paper reports on the process used in La Romana, Dominican Republic, in applying a modified HCP framework. This project succeeded at bringing visiting STEGH organizations into a coalition with key community partners and supported attempts to embed the work of STEGH within longer-term, established development plans. Conclusions In presenting the work and process and lessons learned, the hope is that other communities that encounter significant investment from STEGH groups, and will gain the same benefits that were seen in La Romana with regards to improved information exchange, increased cross-communication between silos, and the integration of STEGH into the work of community partners.